Smart Presentation Control Using Hand Gesture Recognition - Lilis Setyowati; Hans Naufal Granito (Asosiasi Dosen Muda Indonesia, 2025)
Presentation is an activity conducted to express opinions in public, aimed at decision-making or providing new insights on a particular matter. During presentations, audience engagement often suffers due to several disruptions faced by the speaker, such as having to pause to change slides, mismatched transition timing by the moderator when changing slides, and other issues. In order to avoid these distractions, Smart Presentation Feature is designed to provide an effective presentation experience. This feature runs on Windows operating system and is developed using MediaPipe, OpenCV, PyAutoGUI, win32gui module, PyInstaller, and a virtual environment using Miniconda. This feature works by reading the user’s hand gesture to determine the control actions for the presentation. According to a user satisfaction questionnaire consisting of 11 questions, each with 5 criteria ranging from “Strongly Disagree” to “Strongly Agree”, The final score was 89.26% in total, which translates to “Strongly Agree”. This signifies that users are satisfied with the Smart Presentation Feature.